Sclerococcum glaucomarioides: a new geographical record from China - Meng, Qing-Feng; Thiyagaraja, Vinodhini; Ertz, Damien; Worthy, Fiona Ruth; Saichana, Natsaran; Fu, Shao-Bin (Phytotaxa, 2024)
The lichenicolous species Sclerococcum glaucomarioides growing on the lichen Ochrolechia akagiensis is newly reported from China. This study provides an illustration and morphological description for this species, complemented by phylogenetic analyses based on ITS, LSU and mtSSU sequence data. The taxon is characterized by adpressed to sessile apothecia that are round to angular with black disc, hymenium with brownish color, 25–40 μm high, broadly cylindrical to subclavate 8-spored asci, 20–30 × 10–15 μm, with euamyloid apical cap and brown ascospores with 2–3 transverse septa.